Deletion of the CSB homolog, RAD26, yields Spt(–) strains with proficient transcription-coupled repair - Gregory, Sean M. (Oxford University Press, 2001)
It has been previously shown that disruption of RAD26 in yeast strain W303-1B results in a strain that is deficient in transcription-coupled repair (TCR), the preferential repair of the transcribed strand of an expressed gene over the non-transcribed strand and the rest of the genome. RAD26 encodes a protein that is homologous to Cockayne syndrome group B protein (CSB) and is a member of the SWI2/SNF2 family of DNA-dependent ATPases involved in chromatin remodeling. Like the rad26 mutant, cells from Cockayne syndrome patients are defective in TCR. We examined the role of Rad26 in TCR by disrupting RAD26 in two repair-proficient laboratory strains and, remarkably, observed no effect upon TCR. Our results indicate that disruption of RAD26 alone is insufficient to impair TCR. Thus, W303-1B must already possess a mutation that, together with disruption of RAD26, causes a deficiency in TCR. We suggest that other genes are mutated in Cockayne syndrome cells that contribute to the deficiency in TCR. Surprisingly, deletion of RAD26 results in expression of genes that are repressed by flanking transposon δ elements, an Spt(–) phenotype. The δ elements appear to perturb local chromatin structure. Expression of genes flanked by δ elements in rad26Δ mutants is consistent with a role for Rad26 in chromatin remodeling.